Similarity or complementarity? Understanding marital relationships in terms of sexual dimorphism in brain morphometry and gender roles - Lei Li; Xinyue Huang; Qingyu Zheng; Jinming Xiao; Xiaolong Shan; Huafu Chen; Xujun Duan (NeuroImage)
“Birds of a feather flock together” and “opposites attract” are two contrasting statements regarding interpersonal relationships. Sex differences provide a theoretical integration of these two conflicting statements. Here, we explored the relationship between marital satisfaction and sex differences in social attributes and neuroanatomical characteristics in 48 married couples. Sexually dimorphic neuroanatomy was investigated for gray matter volume (GMV), which was estimated by voxel-based morphometry. The brain regions that showed typically larger GMV in males compared with that in females were defined as the male-typical brain regions; otherwise, they were defined as the female-typical brain regions. We found that masculine gender roles and the individual deviation index (IDI) of the GMV in the male-typical brain region were positively correlated with marital satisfaction in males but were negatively correlated in females, demonstrating the “complementarity” nature of masculine characteristics, which was further supported by the negative correlation between couple-wise morphological similarity in male-typical brain region and marital satisfaction. Conversely, feminine characteristics reflected the “similarity” nature of married couples; i.e., feminine gender roles and IDI in the female-typical brain region were positively correlated with marital satisfaction in both males and females, and couple-wise morphological similarity in the female-typical brain region was positively correlated with marital satisfaction. The actor-partner interdependence model also supports the similarity/complementarity hypothesis. Additionally, the sexual dimorphism of brain morphometry and marital satisfaction were found to share a similar transcriptional mechanism. Our findings highlight the relationship among gender roles, brain morphology, and marital satisfaction, providing important implications for understanding marital bonding.